2019
DOI: 10.48550/arxiv.1906.03625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soft-ranking Label Encoding for Robust Facial Age Estimation

Abstract: Automatic facial age estimation can be used in a wide range of real-world applications. However, this process is challenging due to the randomness and slowness of the aging process. Accordingly, in this paper, we propose a comprehensive framework aimed at overcoming the challenges associated with facial age estimation. First, we propose a novel age encoding method, referred to as Soft-ranking, which encodes two important properties of facial age, i.e., the ordinal property and the correlation between adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…9) Crowd Counting: In the video surveillance scenario, it is necessary to count the crowd in both indoor and outdoor areas and prevent crowd congestion and accident. For practical AIoT applications with crowd counting ability, WI-FI, Bluetooth, The processed result by using different perceiving methods, i.e., semantic segmentation [85]; object detection [106]; text spotting [91]; human parsing [86]; human pose estimation [107]; face detection, alignment, and facial attribute analysis [96], [108]; depth estimation [109]. and camera-based solutions have been proposed by estimating the connections between smartphones and WI-FI access points or Bluetooth beacons [126] or estimating the crowd density of a crowd image [127].…”
Section: ) Text Spottingmentioning
confidence: 99%
See 1 more Smart Citation
“…9) Crowd Counting: In the video surveillance scenario, it is necessary to count the crowd in both indoor and outdoor areas and prevent crowd congestion and accident. For practical AIoT applications with crowd counting ability, WI-FI, Bluetooth, The processed result by using different perceiving methods, i.e., semantic segmentation [85]; object detection [106]; text spotting [91]; human parsing [86]; human pose estimation [107]; face detection, alignment, and facial attribute analysis [96], [108]; depth estimation [109]. and camera-based solutions have been proposed by estimating the connections between smartphones and WI-FI access points or Bluetooth beacons [126] or estimating the crowd density of a crowd image [127].…”
Section: ) Text Spottingmentioning
confidence: 99%
“…(a) A frame from the video "Walking Next to People" 11 . (b)The processed result by using different perceiving methods, i.e., semantic segmentation[85]; object detection[106]; text spotting[91]; human parsing[86]; human pose estimation[107]; face detection, alignment, and facial attribute analysis[96],[108]; depth estimation[109].…”
mentioning
confidence: 99%
“…Others have observed that it is easier for a human to distinguish differences in age between two persons, rather than their absolute age and used this as a design principle for ordinal regression [7], [20]. Alternative methods have focused on various soft encodings of the age over classes, where the elements of the probability vector are proportional to the distance from the true class [9], [21], [22]. In this way both the ordinal and metric information can be effectively encoded in the labels.…”
Section: Related Workmentioning
confidence: 99%
“…This problem has been studied in recent works [10,11] as how to learn robust and discriminative facial features through a rather deep neural network with a regularized loss function. However, they do not truly distinguish the confusing and noisy samples from regular ones, and yet not exclude the interference caused by the unreliable samples, resulting in unsatisfactory robustness.…”
Section: Introductionmentioning
confidence: 99%